Management Of Zakat Collection In The Bojonegoro Amil Zakat Agency - Kartika Yustina Mandala Putri; Tri Siwi Agustina (JOURNAL OF SHARIA ECONOMICS, 2023)
The problem of poverty is currently still a classic problem in this country which still cannot be resolved. Poverty is increasingly coming to the fore, especially in various regions in Indonesia as a result of the economic downturn. Thus, of course, a precise and accurate formulation is needed to minimize the poverty rate. In this case, one of the social agendas that Islam actually strives for is the realization of the economic balance of society. Zakat is one of the instruments to make it happen. The research that the researchers did was included in descriptive research with a qualitative approach. The results of the study show that target planning is carried out every month by employees and volunteers of the amil zakat agency. the organization of BAZNAS for Bojonegoro Regency only has a few employees and in the field of collection only has a deputy who is assisted by a deputy in other fields such as a deputy in the financial sector. Implementation of picking up the ball to muzaki, transferring, promoting and establishing good relations with muzaki. Secret supervision by the chairman, if they are directly supervised they will feel supervised and valued, and also if they are not supervised they will feel they are working alone. That's why surveillance was carried out but secretly.